Building Bridges to Oral Communication - Hernández Herrero, Annabelle (2005)
This paper reports the results of a research study carried out with a group of first-year students of English at the School of Modern Languages at the University of Costa Rica. The purpose of the study was to investigate the effects on the students oral production skills of using a combination of reading and listening to texts, and to determine whether or not the proficiency level of the students affects the effectiveness of the technique.